(untitled) (Sound Stage Screen, 2023)
Review of “Alfred Hitchcock’s Psycho Live Orchestra” (Milan, Fondazione Cariplo Auditorium, March 11, 2023). Orchestra Sinfonica Giovanile di Milano conducted by Anthony Gabriele.